Estudio del grado de conocimiento y manejo de las aplicaciones tributarias por parte de las secretarias que laboran en las pymes de la parroquia La Matriz de la ciudad de Latacunga - Pumashunta Gualpa, Ana Lucía (2015)
The small and Medium Enterprises at the Latacunga city “La Matriz” parish “El Salto”area are distributed in different industrial, commercial, and agriculture services; classified by the workers number according to their turnover, social capital, which are the economic power, social and labor development where meets the different needs like the business progress foundation. In the awareness and management study taxes about applications by secretaries who work in the small and Medium Enterprises in the Latacunga city, the integrated methodology was used like approach, techniques and tools, the survey….